Performance and carcass characteristics of different cattles types—A preliminary report - Tuma, H.J.; Allen, Dell M.; May, M.L.; Albrecht, M.D.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station, 2011)
This report contains results from the U.S. Meat Animal Research Center Cattle Germ Plasm Evaluation Program. Dr. Keith Gregory and Dr. Hudson Glimp, U.S. Meat Animal Research Center, Clay Center, Nebraska, initiated and designed the cattle germ plasm evaluation program. Dr. Dan Laster and Dr. John Crouse are currently working on the project from the Research Center. Kansas State University and the Livestock Division, C&MS, U.S.D.A. are cooperating on the project.
Keywords: Beef; Performance; Carcass characteristics; Cattle types